Exploring the Potential for the Arts to Promote Health and Social Justice - Bjørnøy Urke, Helga (2021)
This chapter provides the background and overview for this book Arts and Health Promotion: Tools and Bridges for practice, research and social transformation. We explore the potential for incorporating the arts in the pursuit of the five action areas described in the Ottawa Charter for Health Promotion. We also introduce the 19 contributed chapters included in the volume that describe health promotion projects spanning Asia, Africa, Latin America, Australia, Europe, and North America, promoting the health of diverse populations, including older adults, young people, professionals, whole communities, schoolchildren, divorcees, transgender and nonbinary youth, displaced people/migrants, teachers, and Indigenous peoples. We also describe the metaphor of tools and bridges which guide this book, arguing that art can be a tool to address complex health promotion issues, and also act as bridges across language, culture, and other categories of difference while connecting people to one another in their humanity to promote health and social justice, and to fight inequity and health disparities.